Detection of Rotating Diode Failure Condition & its Protection in Brushless Alternator - S, Pranupa; B M, Kiran Kumar; Rao, S. Nagaraja (International Journal of Engineering and Technology, 2018)
Brushless excitation system is widely used in large capacity synchronous generators since it removes the usage of commutator, brushes and slip rings, hence reduces the losses, maintenance and increases reliability. Rotating Rectifier Assembly (RRA) is the main part of brushless alternator. Due to ageing phenomenon and continuous process regime, diodes in rotating rectifier can fail either due to Open Circuit (OC) or Short Circuit (SC), which overloads the exciter and hence the alternator can no longer run securely. If such condition is prolonged, the Automatic Voltage Regulator (AVR) as well as the exciter windings can be damaged.This paper presents two different methods of diode failure detection in brushless alternators. First method uses an algorithm based on output voltage and the second uses the ripple factor of the exciter field current. Diode failure condition is detected for different type of loads connected to 4 kVA, 380 V, 50 Hz, 4 poles generator with 14 pole exciter (brushless alternator) and the results are verified using MATLAB/Simulink. Also, the protection schemes for rotating diode assembly as well as exciter field windings are presented using Metal Oxide Varistor (MOV) and Discharge Resistor.